Pengaruh Pengayaan Daphnia sp dengan Vitamin C Terhadap Pertumbuhan dan Kelulushidupan Larva Ikan Lele Moma (Clarias meladerma Bleeker, 1846) - Yofangka, Febbiyanti; Nuraini, Nuraini; Sukendi, Sukendi; Heltonika, Benny (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
Blackskin catfish (Clarias meladerma Bleeker, 1846) is one of the endemic freshwater fish that has economic value but this fish has not been cultivated, besides that the problem is that this fish still has slow growth and low survival in the larval stage. One approach that can be taken to increase growth and survival is by administering vitamin C through natural feed enrichment in the form of Daphnia sp., so the aim of this study was to evaluate the impact of giving Daphnia sp. enriched with vitamin C on the growth and survival of blackskin catfish larvae. The research method used was a Completely Randomized Design (CRD) with 4 treatments to wit Daphnia sp. enrichment. with a dose of vitamin C each of 0 mg/L, 150 mg/L, 200 mg/L and 250 mg/L and each treatment was repeated 3 times, for the enrichment process by immersing Daphnia sp. with vitamin C carried out for 3 hours. Rearing of the larvae was carried out in an aquarium with a volume of 10 L of water and a stocking rate of 2 fishes/L with an initial size of larvae 0.70 ± 0,00 cm. During rearing the larvae were fed 4 times a day. The results showed that the administration of Daphnia sp. enriched with vitamin C gave the best growth in the P3 treatment (250 mg/L), specifically the absolute length growth was 0.81 cm better than the control treatment, the absolute weight growth was 0.43 g better than the control treatment, the specific growth rate was 0.54% better than the control treatment and survival 18.4% better than the control treatment. (P<0.05). So based on this study, it was concluded that the enrichment of Daphnia sp. with vitamin C has a positive impact on the growth and survival of blackskin catfish larvae (Clarias meladerma Bleeker, 1846).